Formal and informal markets for water: institutions, performance, and constraints - Easter, K. William; Dinar, Ariel; Rosegrant, Mark W. (1999)
Water markets - either formal or informal - can be an efficient method for reallocating scarce water supplies. At the same time certain constraints can raise the transaction costs of trading water. This paper reviews the conditions necessary to establish successful water markets, identifies potential problems, and offers mitigating strategies. It also uses examples of several informal and formal water markets already in operation to illustrate these problems and the solutions to them. - Reproduced
Keywords: Water supply